Venetoclax concentration affects the incidence of haematological adverse events in patients with acute myeloid leukaemia - Chen, Jing; Yang, Xi; Xie, Jingxian; Zhang, Lijuan; Chen, Lu (Frontiers in Pharmacology, 2026)
IntroductionVenetoclax (VEN) demonstrates considerable inter-individual variability in drug exposure, and its pharmacokinetics are substantially influenced by concurrent administration of CYP3A inhibitors. This study explores the relationship between VEN exposure and the incidence of haematological adverse events (AEs) in patients by quantifying systemic VEN concentrations.MethodsWe retrospectively analyzed data from 114 patients who received VEN therapy. Among these, 52 were treated with VEN combined with azacitidine (AZA, days 1–7), 20 received VEN + AZA combined with omeprazole (OPZ), 20 received VEN + AZA combined with voriconazole (VCZ), and 22 received VEN + AZA combined with posaconazole (PCZ). High-performance liquid chromatography was used to determine the plasma steady-state Cmin and Cmax of VEN (n = 114), and the plasma steady-state Cmin of VCZ (n = 20) and PCZ (n = 22).ResultsThe effect of combined medication on VEN concentration was as follows: VEN + PCZ group/VEN + VCZ group > VEN + OPZ group > VEN group. Increased VEN concentration increased the incidence of Grade 3 or higher haematological AEs. CYP3A inhibitors increased VEN levels, thereby increasing the risk of AEs. A VEN Cmax value of 4,886.00 ng/mL had the highest predictive value for mitigating AEs in patients presenting with Grade ≥3 neutropenia and thrombocytopenia.ConclusionVEN concentration is correlated with the occurrence of haematological AEs, and VEN concentrations can be used to predict the occurrence of haematological AEs.